Economic Freedom and Imperative Requirements in the General Interest-Conflict of Coexistence of Values in European and Polish Economic Law? Remarks Against the Background of Cross-Border Business Activities of Companies in the European Union - Pokryszka, Katarzyna (Review of European and Comparative Law, 2023)
Economic freedom is one of the basic principles of Poland’s economic system and, at the same time, a fundamental rule on which the functioning of the European Union’s internal market is based. In the judgment in Case C-106/16 Polbud, which was issued on the basis of Polish law, the Court of Justice confirmed the possibility for companies to carry out activities in the territories of EU Member States in the form of a cross-border conversion into a company governed by the law of another Member State, and stressed the need for Member States to verify the restrictions imposed on companies in connection with their cross-border activities in terms of their compliance with EU law. The article focuses on analysis of the idea of economic freedom in the context of cross-border business activities of companies and on the presentation of the concept of “imperative requirements in the general interest” as conditions determining the admissibility of restrictions on cross-border activities of companies by the company’s home State in the light of European Union and Polish law.